Perbandingan Proses Pengolahan Air Secara Manual Dan Sistem Scada Perumda Tirta Mayang Kota Jambi - Siti Umi Kalsum; Anggrika Riyanti; Adiba Alippia Zainanda (Universitas Batanghari Jambi, 2022)
PERUMDA Drinking Water Tirta Mayang Jambi City has two processing systems, namely a manual system and SCADA system (suvervisory control and data aqustion) both systems have a manual processing capacity with a capacity of 300 l/d while the SCADA system with a capacity of 600 l/d. The result of the two water treatment systems show differences in terms of operating units and process units as well as water quality parameters include pH, residual chlorine and turbidity. The purpose of this research is to know the difference between manual system and SCADA system water treatment processat PERUMDA drinking water Tirta Mayang Jambi City. The method used is comparative quantitative analysis which compares the existence of one or more variables in two or more different samples, or at different times. The results showed that there was a significant difference in the burbidity parameter at a percentage of 10-40% between the manual system and the SCADA system, the effect of seasons also had an effect on turbidity. Where in the rainy seasons the quality of water turbidity increases significantly compared to the dry season.